2004
DOI: 10.1002/path.1521
|View full text |Cite
|
Sign up to set email alerts
|

In ovarian neoplasms, BRAF, but not KRAS, mutations are restricted to low‐grade serous tumours

Abstract: Genes of the RAF family, which mediate cellular responses to growth signals, encode kinases that are regulated by RAS and participate in the RAS/RAF/MEK/ERK/MAP-kinase pathway. Activating mutations in BRAF have recently been identified in melanomas, colorectal cancers, and thyroid and ovarian tumours. In the present study, an extensive characterization of BRAF and KRAS mutations has been performed in 264 epithelial and non-epithelial ovarian neoplasms. The epithelial tumours ranged from adenomas and borderline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
189
5
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(212 citation statements)
references
References 14 publications
15
189
5
3
Order By: Relevance
“…Mutation in other genes, including FAT3, CSND3, NF1, CDK12, RB1 and GABRA6, are also frequently identified in HGSOC tumours 15. Mutations in BRAF are restricted to serous borderline tumours, indicating that the majority of serous borderline tumours do not progress to serous carcinomas 33. Activating KRAS mutations are more common in mucinous tumours than in all other histological types 17, 34, while no mucinous tumours have been found to harbour a BRAF mutation 34.…”
Section: Molecular Portraits Underlying Th Of Eocmentioning
confidence: 99%
“…Mutation in other genes, including FAT3, CSND3, NF1, CDK12, RB1 and GABRA6, are also frequently identified in HGSOC tumours 15. Mutations in BRAF are restricted to serous borderline tumours, indicating that the majority of serous borderline tumours do not progress to serous carcinomas 33. Activating KRAS mutations are more common in mucinous tumours than in all other histological types 17, 34, while no mucinous tumours have been found to harbour a BRAF mutation 34.…”
Section: Molecular Portraits Underlying Th Of Eocmentioning
confidence: 99%
“…[38][39][40][41][42]44,45 Serous borderline tumors have a higher rate of KRAS mutations (27-36%) than high-grade serous carcinomas (0-12%). 40,46,47,[75][76][77][78] BRAF mutations, which are seen in 33-50% of serous borderline tumors of typical or micropapillary type, have not been identified in high-grade serous carcinoma. 74,76,78 A few studies analyzing and comparing serous borderline tumors and low-grade serous carcinomas have been performed only recently.…”
Section: Molecular Genetic Datamentioning
confidence: 99%
“…40,46,47,[75][76][77][78] BRAF mutations, which are seen in 33-50% of serous borderline tumors of typical or micropapillary type, have not been identified in high-grade serous carcinoma. 74,76,78 A few studies analyzing and comparing serous borderline tumors and low-grade serous carcinomas have been performed only recently. These studies have found a similar frequency of KRAS mutations in approximately one-third of typical or micropapillary serous borderline tumors and invasive lowgrade serous carcinomas (invasive micropapillary serous carcinoma), and BRAF mutations in an additional similar proportion.…”
Section: Molecular Genetic Datamentioning
confidence: 99%
See 2 more Smart Citations